The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12913-018-3653-1
|View full text |Cite
|
Sign up to set email alerts
|

Using behaviour change and implementation science to address low referral rates in oncology

Abstract: BackgroundPatients undergoing surgery for bowel cancer now have a routine screening test to assess their genetic predisposition to this and other cancers (Lynch syndrome). A result indicating a high risk should trigger referral to a genetic clinic for diagnostic testing, information, and management. Appropriate management of Lynch syndrome lowers morbidity and mortality from cancer for patients and their family, but referral rates are low. The aim of this project was to increase referral rates for patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…However, the research team connected weekly with the two participating hospitals to facilitate access through ethics and governance approvals, establish implementation teams, lead process mapping exercises, coordinate audit data collection, distribute questionnaires, drive intervention development, and support implementation. Based on this work, while the referral processes improved, the primary outcome measure—proportion of appropriate referrals—was largely unchanged …”
Section: Introductionmentioning
confidence: 99%
“…However, the research team connected weekly with the two participating hospitals to facilitate access through ethics and governance approvals, establish implementation teams, lead process mapping exercises, coordinate audit data collection, distribute questionnaires, drive intervention development, and support implementation. Based on this work, while the referral processes improved, the primary outcome measure—proportion of appropriate referrals—was largely unchanged …”
Section: Introductionmentioning
confidence: 99%
“…An estimated 53% of Australian laboratories are yet to adopt a universal Lynch syndrome tumour testing strategy [18], and even when tumour testing is performed, genetic referral rates for those with abnormal results (indicating a high risk of Lynch syndrome) are poor. Two recent Australian studies demonstrated that a minority (34% and 26%, respectively) of colorectal cancer patients with abnormal tumour test results were referred for genetic counselling and testing [16,17]. Similar findings have also been demonstrated in the international setting [19][20][21], highlighting a need for implementation interventions to improve genetic referral and Lynch syndrome diagnosis.…”
Section: Morrow Et Al Implementation Science Communicationsmentioning
confidence: 56%
“…Based on an indicative willingness-to-pay threshold of $30,000-$50,000 per LYS, this approach is likely to be considered costeffective by decision makers [14]. Despite this, uptake of the Lynch syndrome tumour testing and referral pathway remains suboptimal [15][16][17]. An estimated 53% of Australian laboratories are yet to adopt a universal Lynch syndrome tumour testing strategy [18], and even when tumour testing is performed, genetic referral rates for those with abnormal results (indicating a high risk of Lynch syndrome) are poor.…”
Section: Morrow Et Al Implementation Science Communicationsmentioning
confidence: 99%
“…Furthermore, the tool has been used successfully to identify barriers in the context of LS in the HaSP pilot study. 32 The IPSBQ will be distributed by Implementation Leads to LS stakeholders at each hospital network at time points before and after the intervention implementation to assess for changes in perceived LS referral barriers. Implementation Leads will be encouraged to seek a large sample (approximately 20-40, depending on hospital network size) with representation from each of the key departments involved in the LS referral pathway to ensure correct identification of key barriers.…”
Section: Influences On Patient Safety Behaviours Questionnairementioning
confidence: 99%